Book citations: influence of epidemiologic thought in the academic community - Miquel Porta; Esteve Fernandez; Elisa Puigdomènech
Whilst their 'death' has often been certified, books remain highly important to most professions and academic disciplines. Analyses of citations received by epidemiologic texts may complement other views on epidemiology. The objective was to assess the number of citations received by some books of epidemiology and public health, as a first step towards studying the influence of epidemiological thought and thinking in academia. For this purpose, Institute for Scientific Information/ Thomson Scientific - Web of Science/ Web of Knowledgedatabase was consulted, in May 2006. The book by Rothman & Greenland appeared to have received the highest number of citations overall (over 8,000) and per year. The books by Kleinbaum et al, and by Breslow & Day received around 5,000 citations. In terms of citations per year the book by Sackett et al ranks 3rd, and the one by Rose, 4th of those included in this preliminary study. Other books which were influential in the classrooms collected comparatively less citations. Results offer a rich picture of the academic influences and trends of epidemiologic methods and reasoning on public health, clinical medicine and the other health, life and social sciences. They may contribute to assess epidemiologists' efforts to demarcate epidemiology and to assert epistemic authority, and to analyze some historical influences of economic, social and political forces on epidemiological research.